Implementation of a Differentiated Approach to the Subject of Islamic Cultural History at Madrasah Ibtidaiyah - Krisetyaningsih, Krisetyaningsih; Nurlaili, Nurlaili; Mardeli, Mardeli; Faisal, Faisal; Wasilah, Wasilah (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study aims to analyze the implementation of differentiated learning approaches in class V SKI subjects at MI Al-Adli and MI Munawariyah Palembang. The research employed a qualitative approach with a multisite method, incorporating in-depth interviews, structured observations, and document analysis with participants including madrasah heads, deputy heads of curriculum, teachers, conducteddents. Data analysis involved using thematic analysis, categorization, and cross-case analysis to identify similarities and differences in implementation in the two madrasas. The results showed that teachers had implemented differentiation of content, processes, and products. However, the implementation was not fully optimal due to limitations in diagnostic assessments, learning facilities, and the application of differentiation. Differentiation can enhance learning motivation, historical understanding, and active student participation. These findings reinforce the importance of implementing differentiated learning in SKI and show the need to ensure consistent and sustainable implementation.